Partnering in construction as governance tool - Roders, Martin (A+BE | Architecture and the Built Environment, 2015)
Climate change can no longer be ignored. It is globally recognised that the evidence for climate change is unequivocal (IPCC, 2014) and action needs to be taken to address its negative consequences (UNFCCC, 2011). The challenge of stimulating this action is taken up by this thesis - albeit at the level of individual buildings rather than at the global level - by engaging the construction sector in the implementation of adaptation measures in the social housing stock. To achieve this, the research fields of climate change adaptation, governance and partnering in construction are brought together. The effects of climate change in the Netherlands were briefly explained in the introduction and will be further elaborated in Chapter 3.